Risk factors for severe bleeding events during warfarin treatment: the influence of sex, age, comorbidity and co-medication - Rydberg, Diana M. (Eur J Clin Pharmacol, 2020)
PURPOSE: To investigate risk factors for severe bleeding during warfarin treatment, including the influence of sex, age, comorbidity and co-medication on bleeding risk. METHODS: Patients initiating warfarin treatment between 2007 and 2011 were identified in the nationwide Swedish Prescribed Drug Register, and diagnoses of severe bleeding were retrieved from the National Patient Register. Hazard ratios (HR) with 95% confidence intervals (CI) for severe bleeding were estimated using multiple Cox regression adjusting for indications and including covariates age, sex, comorbidities and co-medications. Interactions between sex and other covariates were investigated. RESULTS: The study cohort included 232,624 patients ≥ 18 years (101,011 women and 131,613 men). The incidence rate of severe bleeding was 37 per 1000 person-years, lower among women than men with an adjusted HR (95% CI) of 0.84 (0.80–0.88). Incidence of bleeding increased with age, HR 2.88 (2.37–3.50) comparing age ≥ 80 to < 40 years, and comorbidities associated with the highest risk of severe bleeding were prior bleeding, HR 1.85 (1.74–1.97); renal failure, HR 1.82 (1.66–2.00); and alcohol dependency diagnosis, HR 1.79 (1.57–2.05). Other comorbidities significantly associated with bleeding events were hypertension, diabetes, peripheral vascular disease, congestive heart failure, liver failure, stroke/TIA, COPD and cancer. CONCLUSION: Most of the well-established risk factors were found to be significantly associated with bleeding events in our study. We additionally found that women had a lower incidence of bleeding. Potential biases are selection effects, residual confounding and unmeasured frailty. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00228-020-02856-6) contains supplementary material, which is available to authorized users.